Resilient Consensus Control for Linear Multi-agent System Against the False Data Injection Attacks - Wang, Meirong; Hu, Jianqiang; Cao, Jinde (International journal of control, automation, and systems, 2023)
This paper is concerned with the resilient consensus control problem of the linear multi-agent system under the false data injection attacks, where each agent may receive the injected false data by attackers from its neighbours through communication links. Due to the existence of the false data, the desired consensus of multi-agent can not be reached by the general distributed consensus algorithms. By constructing an extended state observer to estimate the state and the injected false data towards each agent, a distributed resilient consensus control algorithm is designed to offset the negative effect of the attacks. Firstly, a sufficient condition is derived for the undirected multi-agent system under a bounded and decaying false data injection. Secondly, a sufficient and necessary condition is provided for the directed multi-agent system under the false data injection with decaying rate. Finally, the simulation results illustrate the effectiveness of the proposed consensus algorithms against the false data attacks.